The Influencing Factors To Abortion Event At Rsud Dr. H. Moch Ansari Saleh Banjarmasin In 2017 - Eka ayuning (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2022)
The influencing factors to abortion event are parity, maternal age and abortion history. Abortion event rate at RSUD Dr. H. Moch Ansari Saleh Banjarmasin in 2015 of 205 people (4.9%), 2016 of 224 people (5.8%) and 2017 of 171 people (7.9%) who had abortion. This shows that this event has increased 3% in 2015-2017. This study aimed to determine the influencing factors to abortion event at RSUD Dr. H. Moch. Ansari Saleh Banjarmasin in 2017. The study method used analytic survey, with case control approach. The population was all maternal at RSUD Dr. H. Moch Ansari Saleh Banjarmasin in 2017 as many as 2114 people. Case study sample was maternal with abortion event of 171 people and control study sample was mother who gave birth of 171 people, their comparison of them 1:1. The study sampling was Systematic Random. Data analysis technique used chi square statistic test. The study result was obtained from 342 mother of 252 people (73,7%) was age not risk, unsafe parity 237 people (69,3%) and no abortion history 267 people (78,1%). Statistical test result showed correlation to age (ρ 0,000), parity (p 0,019), abortion history (p 0,000) with abortion event. The conclusion of the study was the correlation among age, parity and abortion history with abortion event at RSUD Dr. H. Moch Ansari Saleh Banjarmasin.